ENVIRONMENTAL CONCERNS: COVID-19 RELATED AIR POLLUTION - Athiyyah Romiizah; Skunda Diliarosta (Pendidikan IPA, FMIPA, UNP, 2020)
Air is a major factor directly related to living things. Ordinary air is composed of oxygen, nitrogen, carbon dioxide, argon and other gases. Good air can make the sky not dark and foggy. However, the air now that we breathe is already unhealthy, because it has been polluted by the smoke of vehicles using gasoline, and added to the corona virus (Coronavirus Disease 2019) in the air. The journal will discuss air pollution reviewed from pollution sources, their impacts, and how to deal with them. In addition, it also explained Covid indicators of air pollution related to Covid-19 and the understanding of air pollution. It is hoped that this journal can provide information for all of us, so as to reduce air pollution that occurs and Covid-19 that is in the air is also immediately lost. © Departemen Pendidikan Sains Universitas Negeri Padang